‘Distressed Protestants or Irish vagrants?’ Charity and the organisation of relief to ‘Irish’ refugees in England, 1641-1651. - Marsh, Bethany (2019)
On the evening of 22 October 1641 organised rebellion broke out in Ireland precipitating the displacement of thousands of Protestant refugees. While many remained internally displaced in Ireland, over the course of the 1640s a significant number of these refugees subsequently fled to England, Scotland and the Continent in search of safety, security and relief. Few studies have hitherto considered these refugees in great depth and those which have been conducted make several assumptions about the refugees. Typically, the refugees are treated as a homogenous group of returning migrants and the attitudes of the English towards the refugees is viewed as largely dichotomous; the refugees were considered either ‘distressed Protestants’ or ‘evil Irish’. This thesis extends and challenges the previous historiography, offering a more comprehensive view of the reception of the refugees in England. The focus of the thesis centres on three main research questions: 1) Who were the refugees from Ireland? 2) How was relief in England organised and dispensed? 3) What does the organisation and dispensation of relief reveal about English attitudes towards the refugees from Ireland? Local parish churchwardens’ and constables’ accounts form the principal source base for this research. Quantitative analysis of parish relief in these documents allows for a comparative study of parishes across England, highlighting regional variations in aid and refugee migration patterns – areas of enquiry that have never previously been considered by historians. This analysis also shows how local parish officials were able to balance the provision of aid to refugees with the complex web of local political, economic and social concerns, in the context of the upheaval of the British and Irish Civil Wars. Ultimately, this thesis will reveal that English attitudes towards the refugees were far more nuanced than the dichotomous view of ‘distressed Protestants’ or ‘Irish vagrants’.